2003
DOI: 10.1046/j.1523-1755.2003.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of renal tubular electrolyte transporter genes in seven patients with hypokalemic metabolic alkalosis

Abstract: Our findings demonstrate that in Bartter's and Gitelman's syndromes, it may not be uncommon to see mutations in several causative transporter genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…Recently, Schlingmann (20) has reported a case with mutations in two genes involved in renal salt transport: a child with renal salt losing tubulopathy and deafness did not show defects on the Barttin gene, but had homozygous mutations on both the ClC-Ka and -Kb chloride channels. Fukuyama et al (21) hypothesized that GS and BS patients frequently show mutations in more than one of the involved transporter genes but, in our view, the patients described in their paper must be considered as polymorphism carriers as Jeck et al (22) subsequently demonstrated that three of the four amino acid variants were common sequence variations without any functional effect in an expression system study. Heterozygote for CLCNKB and SLC12A3 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schlingmann (20) has reported a case with mutations in two genes involved in renal salt transport: a child with renal salt losing tubulopathy and deafness did not show defects on the Barttin gene, but had homozygous mutations on both the ClC-Ka and -Kb chloride channels. Fukuyama et al (21) hypothesized that GS and BS patients frequently show mutations in more than one of the involved transporter genes but, in our view, the patients described in their paper must be considered as polymorphism carriers as Jeck et al (22) subsequently demonstrated that three of the four amino acid variants were common sequence variations without any functional effect in an expression system study. Heterozygote for CLCNKB and SLC12A3 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this mutation has been reported to be responsible for GS in at least three reports (11−13). Monkawa et al (11) reported that 1 of their 6 subjects with GS (from Tokyo and Tochigi) was heterozygous for this mutation, Fukuyama et al (12) reported that 1 of their 7 GS subjects (from Okinawa) was heterozygous for it, and Maki et al (13) reported that 2 of their 8 GS subjects (from Akita) showed compound heterozygosity for the mutation. This reproducibility further strengthens the hypothesis that the L849H mutation is responsible for GS.…”
Section: Discussionmentioning
confidence: 99%
“…All exons and exon-intron boundaries of the CLCNKB and SLC12A3 genes were amplified by polymerase chain reaction and direct sequencing using previously described primer pairs. 10,17 Patients suspected to have BS/GS with no CLCNKB or SLC12A3 mutations were diagnosed as having p-BS/GS. If patients suspected to have BS/GS carried only one CLCNKB or SLC12A3 mutant allele, we performed additional semiquantitative polymerase chain reaction 10,18 or multiplex ligation-dependent probe amplification using the SALSA P266-CLCNKB or P136-SLC12A3 multiplex ligation-dependent probe amplification assays (MRC-Holland, Amsterdam, The Netherlands) to detect large heterozygous deletions.…”
Section: Mutational Analysesmentioning
confidence: 99%